Laporan latihan praktik di Data Services Unit TMco Seberang Jaya 13700 Seberang Jaya Pulau Pinang / Mohd Izwan Mahmud - Mahmud, Mohd Izwan (Universiti Teknologi MARA, Kedah, 2006)
I have successfully completed my practical training in TM Pulau Pinang for duration of full four working months which is from 3rd July 2006 until 20th October 2006. I was located in Data Service Unit (DSU) TM Seberang Jaya for four full working months. I have learned on the data services provided by DSU such as DA, DQ, and DG. Other than that, I have been taught about circuit types and Network Terminating Unit used by data service group. In this unit, I have practiced on circuit testing using Network Management System (NMS) and dummy circuits. I also assisted the field team on the installation and restoration of Data Services. By the end of the training; I was given a task to make a new installation for low speed circuit, and prepared a layout of the configuration. Upon the completion of my training in this unit, I was able to understand and differentiate between all the three services provided by data services group and understand the overall process in installation and restoration of network equipment by DSU.